Substance use disorders, severe mental illness and risk of reoffending among women released from prison: a national cohort study - Vegard Svendsen; Marianne Riksheim Stavseth; Torbjørn Skardhamar; Ingrid Amalia Havnes; Anne Bukten (Scientific Reports)
Abstract Women with a clinical history of a severe mental illness (SMI) or multiple mental disorders involving substance use disorder (SUD) might be at increased risk of re-offending after release from prison. This retrospective cohort study merged data from the Norwegian prison release study (nPRIS) with other registry sources. All women released from a Norwegian prison between 2011–2019 were followed for two years after date of release. Adjusting for several known risk factors, we used logistic regression to estimate risk of violent (VR), drug-related (DR) or other reoffending (ORE) after release among women with a history of SUD and severe mental illness (SUD-SMI), SMI, SUD and other mental illness (SUD-OMI) or a history of multiple SUDs (POLY-SUD) in comparison to a reference population with no history of such disorders or combination of disorders. Relative to the reference population, after adjusting for other relevant risk factors, women with a history of SUD-SMI (ORVR 2.27, 95% CI 1.37–3.76; ORDR 2.10, 95% CI 1.49–2.95), SUD-OMI (ORVR 1.81, 95% CI 1.11–2.47; ORDR 1.53, 95% CI 1.11–2.10) or POLY-SUD (ORVR 1.87, 95% CI 1.04–3.31; ORDR 2.51, 95% CI 1.80–3.49) were at significantly greater risk of violent and drug-related reoffending. Women with a history of SMI were at significantly greater risk of other reoffending (ORORE 2.64, 95% CI 1.21–5.30). Women with a clinical history of a severe mental illness (SMI) or multiple mental disorders involving substance use disorder (SUD) have an elevated risk reoffending.